Persepsi Mahasiswa Pendidikan Biologi Universitas Katolik Widya Mandira Terhadap E-Learning Pada Masa Pandemi Covid-19 - Simon Paskalis Kun; Aloysius Djalo; Hildegardi Missa (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2022)
The learning process using electronic learning (e-learning) can be done remotely, without having to meet face to face in the room directly, and the learning time is more flexible. Biology Education Widya Mandira Catholic University is one of the parties who feel learning using e-learning, but in reality there are still many students who do not understand the use of e-learning in the learning process, this of course will affect the learning process carried out by lecturers and students if not overcome. The purpose of this study was to determine student perceptions of the Widya Mandira Catholic University Biology Education Study Program towards Learning using e-learning during the Covid 19 Pandemic. This study uses a qualitative approach, sampling is done by purposive sampling technique, data collection techniques are carried out by filling out questionnaires through google forms and interviews to find out obstacles in learning using e-learning. The results showed that the perception of students of the Widya Mandira Catholic University Biology Education Study Program towards learning using e-learning obtained an average perception score of 59,69% with a good category. The conclusion of this study is the students' perception of learning using e-learning is in a fairly good category with an average perception value of 59,69% this is because some students feel they do not understand the learning materials, the time provided is not in accordance with the existing credits, learning using e-learning requires internet or wifi packages, and lack of interaction between lecturers and students.